EMPOWERING CHILDREN WITH SPECIAL NEEDS THROUGH SENSORY LEARNING: A CREATIVE THERAPEUTIC MEDIA TO FOSTER MOTIVATION AND ASPIRATIONS - Sitti Sulaihah; Uswatun Hasanah; Moh Zainal Arifin; Evi Kumala Sari; Lelly Febriyanti Rifama; Moh Eko Wahyudi (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2026)
Introduction: Children with Special Needs at SLB Negeri Keleyan Bangkalan experience various challenges such as communication difficulties, emotional regulation issues, low self-confidence, and limited opportunities for self-expression. This study aims to develop and implement an expressive and therapeutic learning medium to improve emotional expression, emotional regulation, self-confidence, and learning motivation. Methods: The community service program SLIME ASA (Sensory Learning to Improve Exploration and Aspiration) was developed as a sensory therapy intervention using slime to stimulate sensory exploration, imagination, emotional expression, and motivation. The program design used a pre–post observational approach. The subjects of this program were all Children with Special Needs at SLB Negeri Keleyan Bangkalan, totaling 51 students. The variables measured in this program included activity motoric, participation rate, and parental support. Data were collected using observation sheets and analysis by comparing the pre- and post-observation. Results: A significant improvement in participation, increasing from 25% to 83.30%, and fine motor skills in the “very good” category improved from 43% to 52.94%. The children showed greater confidence, positive emotional expression, and willingness to perform in front of others. Conclusion: The SLIME ASA program provides tactile, proprioceptive, and visual input that help children recognize, manage, and express their emotions more adaptively. The play-based therapy approach encourages active engagement, creative exploration, and experiences of small successes, which gradually strengthen children’s self-confidence. Social interaction during the activities also contributes to improving communication skills, emotional regulation, and interpersonal relationships. KEYWORDS children with special needs; inclusive learning; self-expression; sensory therapy; SLIME ASA